Dynamics of Financial Inclusion and Economic Growth in Nigeria: Insights from Liquidity, Credit Allocation and Lending Rate - Gideon Olugbenga Torila; Olukayode Abiodun Bilewu; Olusola Enitan Olowofela (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
Financial inclusion is recognized as a key driver of economic growth, particularly in developing economies like Nigeria. This study investigates the impact of financial inclusion on Nigeria’s economic growth by examining indicators such as Gross Domestic Product (GDP), Loan-to-Deposit Ratio (LDR), Money Supply (MS), Credit to the Private Sector (CRED) and Lending Rate (LR). The study employs econometric techniques, including co-integration tests and dynamic least squares regression, to evaluate long-term relationships between financial inclusion and economic growth utilizing secondary data from 1991 to 2024. The findings suggest that while money supply positively influences economic growth, credit allocation inefficiencies, high lending rates and financial exclusion hinder Nigeria’s economic expansion. The results highlight the need for policy interventions to enhance financial access, improve credit allocation and promote financial literacy. Strengthening financial inclusion strategies can lead to sustainable economic development, poverty reduction and enhanced financial stability. This study provides valuable insights for policymakers, financial institutions and development agencies in Nigeria.